2010
DOI: 10.1510/icvts.2010.234013
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo cardiomyopathy after elective mitral valve replacement

Abstract: Takotsubo cardiomyopathy is a syndrome characterized by transient acute left ventricular dysfunction, electrocardiographic changes that can mimic acute myocardial infarction and minimal release of myocardial enzymes in the absence of obstructive coronary artery disease. Reports of Takotsubo syndrome after cardiac surgery are exceptional. We describe a case of Takotsubo cardiomyopathy in a 68-year-old woman after elective mitral valve replacement. Takotsubo syndrome should be considered in the differential diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 7 publications
0
20
0
1
Order By: Relevance
“…5 Belazquez et al in Spain observed apical ballooning syndrome after elective mitral valve replacement. 6 Wong in Hong Kong described Takotsubo syndrome after extirpation of a left atrial myxoma. 7 It is possible that some cases of transient left ventricular sphericalization after mi-tral valve replacement, which remained unexplained before the recognition of this phenomenon, were cases of Takotsubo syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…5 Belazquez et al in Spain observed apical ballooning syndrome after elective mitral valve replacement. 6 Wong in Hong Kong described Takotsubo syndrome after extirpation of a left atrial myxoma. 7 It is possible that some cases of transient left ventricular sphericalization after mi-tral valve replacement, which remained unexplained before the recognition of this phenomenon, were cases of Takotsubo syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Several cases of TTC have been described in the literature. TTC have been reported particularly in association with general anesthesia; 9-12 surgical interventions including laparoscopic cholecystectomy, total gastrectomy, mitral valve replacement, and paranasal sinus surgery; [13][14][15][16][17] clinical situations including MRSA meningitis, acute diarrhea, thyroid storm, pheochromocytoma, status asthmaticus, acute pericarditis, seizures, Guillaine Barre, multiple myeloma, cerebrovascular accident, coughing, and near drowning; 6,[18][19][20][21][22][23][24][25][26][27][28] exposure to various medications; and methadone withdrawal. 29,30 Each case of the above situations is capable to induce a significant emotional stress.…”
Section: Discussionmentioning
confidence: 99%
“…Blàzquez et al described one of the first cases of TC occurring after elective mitral valve replacement. At the end of uneventful cardiopulmonary bypass, prosthetic mitral valve function and left ventricular contraction were normal on transesophageal echocardiography.…”
Section: Takotsubo Cardiomyopathy and Cardiac Surgerymentioning
confidence: 99%
“…Administration of beta blockers is indicated in order to increase diastolic ventricular filling time and left ventricular end‐diastolic volume. Phenylephrine administration may increase afterload with subsequent reduction of the intraventricular gradient …”
Section: Takotsubo Cardiomyopathy and Cardiac Surgerymentioning
confidence: 99%